2009
DOI: 10.1186/1471-2296-10-9
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and cost-effectiveness of an educational intervention for practice teams to deliver problem focused therapy for insomnia: rationale and design of a pilot cluster randomised trial

Abstract: Background: Sleep problems are common, affecting over a third of adults in the United Kingdom and leading to reduced productivity and impaired health-related quality of life. Many of those whose lives are affected seek medical help from primary care. Drug treatment is ineffective long term. Psychological methods for managing sleep problems, including cognitive behavioural therapy for insomnia (CBTi) have been shown to be effective and cost effective but have not been widely implemented or evaluated in a genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Simplified Personal Questionnaire (PQ). The PQ (Elliott, Mack, & Shapiro, 1999;Shapiro, 1961) is an outcome measure meant to assess changes in the problems that patients report when they seek treatment. The PQ items are generated in a pretreatment semistructured interview, where the patient reports a list of problems that motivated him or her to seek therapy.…”
Section: Patient-generated Outcome Measuresmentioning
confidence: 99%
“…Simplified Personal Questionnaire (PQ). The PQ (Elliott, Mack, & Shapiro, 1999;Shapiro, 1961) is an outcome measure meant to assess changes in the problems that patients report when they seek treatment. The PQ items are generated in a pretreatment semistructured interview, where the patient reports a list of problems that motivated him or her to seek therapy.…”
Section: Patient-generated Outcome Measuresmentioning
confidence: 99%
“…Understanding the relationship between sleep hygiene and sleepiness will widen the avenue into the therapy of sleep problems regardless of etiology. Recent literature suggests the role of nonpharmacological therapies is important in treating many sleep problems (Azad, Byszewski, Sarazin, McLean, & Koziarz, 2003;Chesson et al, 1999;Harsora & Kessmann, 2009;Hoch et al, 2001;Siriwardena et al, 2009;Stepanski & Wyatt, 2003;Weiss, Wasdell, Bomben, Rea, & Freeman, 2006;Wildschiodtz & Rasmussen, 1981). Further, clarifying the sleep hygienesleepiness relationship should be particularly useful in population groups where hours are long and/or unpredictable, such as resident doctors, shift work employees, IT and BPO professionals.…”
mentioning
confidence: 99%
“…Other economic evaluation literature has focused on interventions designed to provide education to health care providers (). Often, these interventions have included training on specialty care services such as insomnia care (), smoking cessation (), and hypertension prevention and control () for PCPs. These studies have found that, relative to usual care, training yielded ICERs between $25 and $54,755 per life year gained.…”
Section: Discussionmentioning
confidence: 99%